2004
DOI: 10.1590/s0104-66322004000400006
|View full text |Cite
|
Sign up to set email alerts
|

A numerical simulation analysis of the effect of the interface drag function on cluster evolution in a CFB riser gas-solid flow

Abstract: -The dynamics of formation, dissipation and breaking of coherent structures in the riser gas-solid flow of a circulating fluidized bed (CFB) are evaluated by numerical simulation. The simulation is performed using the MICEFLOW code, which includes IIT's two-fluid hydrodynamic model B. The methodology for cluster characterization is used from Sharma et al. and is based on determination of four characteristics, average lifetime, average volumetric fraction of solid, existence time fraction and frequency of occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…It is usually the primary force to suspend and transport the particles and have significant influence on the results. For example Benyahia [9], Gomez and Milioli [10], Heynderickx et al [11] and Wang et al [12] compared solid-volume-fraction variations in the riser of circulating fluidized bed and observed that the drag laws based on empirical relations give more homogenous structures as compared to experiments. Du et al [13] compared voidage profiles, particle velocity profiles and solid flow patterns in spouted beds and observed different results by different drag relations.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually the primary force to suspend and transport the particles and have significant influence on the results. For example Benyahia [9], Gomez and Milioli [10], Heynderickx et al [11] and Wang et al [12] compared solid-volume-fraction variations in the riser of circulating fluidized bed and observed that the drag laws based on empirical relations give more homogenous structures as compared to experiments. Du et al [13] compared voidage profiles, particle velocity profiles and solid flow patterns in spouted beds and observed different results by different drag relations.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other models, in case of particles nonspherical in shape, the coefficient of sphericity / s can be introduced. [3,18] The issue of sphericity coefficient is discussed later in the article. An interesting expanded mathematical model, based on the Ergun equation, is described in Béttega et al [19] The Richardson-Zaki drag model (1954) has the form of: [6] b fs ¼…”
Section: Review Of Momentum Exchange Modelsmentioning
confidence: 99%
“…The resistance of the surrounding is determined most frequently from the Schiller-Neumann formula: [3,4,13,14,16,20] C D ¼ where Re s is the local Reynolds number:…”
Section: Review Of Momentum Exchange Modelsmentioning
confidence: 99%
See 2 more Smart Citations